The effect of game-based exercises on upper extremity muscle strength, tactile gnosia, and functionality: A randomized controlled study. - Kilicoglu, Emine Arslan; Unuvar, Bayram Sonmez (Work, 2025)
Background: Upper extremity rehabilitation often involves exercises aimed at improving muscle strength, tactile gnosia, and functionality. Game-based exercises (GBE) have emerged as a novel approach to rehabilitation, offering engaging activities that may enhance patient motivation and compliance. Objective: This randomized controlled study aimed to investigate the effect of GBE on upper extremity muscle strength, tactile gnosia, and functionality. Methods: Participants were randomly assigned to either GBE group (n = 20) or control group (CG) (n = 20). The GBE group engaged in game-based exercises twice a week for six weeks, while the CG received no intervention. Upper extremity muscle strength was assessed using a Jamar Hand Dynamometer for grip strength and a Hydraulic Pinch Gauge for pinch strength assessments. Tactile gnosia was assessed using the Static Two-Point Discrimination (2PD) Threshold test. Functionality was assessed using the Nine-Hole Peg Test (9HPT). Results: The GBE group showed a significant increase in grip strength (p <.001) and pinch strength (p <.001) compared to baseline, while no significant changes were observed in the CG. Additionally, the GBE group demonstrated a significant improvement in tactile gnosia as assessed by the 2PD test (p <.001). Furthermore, a significant improvement in functionality, as indicated by decreased 9HPT completion times, was observed in the GBE Group (p <.001). Conclusions: Game-based exercises have a positive effect on upper extremity muscle strength, tactile gnosia, and functionality. These findings suggest that incorporating GBE into rehabilitation programs may be beneficial for individuals seeking to improve upper extremity function. Further research with larger sample sizes and longer durations is recommended to validate these findings and explore their long-term effects.